The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1462-2920.15915
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of greigite and pyrite induced by Thermococcales: an advantage to live in Fe‐ and S‐rich environments?

Abstract: Summary Thermococcales, a major order of archaea inhabiting the iron‐ and sulfur‐rich anaerobic parts of hydrothermal deep‐sea vents, have been shown to rapidly produce abundant quantities of pyrite FeS2 in iron–sulfur‐rich fluids at 85°C, suggesting that they may contribute to the formation of ‘low temperature’ FeS2 in their ecosystem. We show that this process operates in Thermococcus kodakarensis only when zero‐valent sulfur is directly available as intracellular sulfur vesicles. Whether in the presence or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 101 publications
(152 reference statements)
4
14
0
Order By: Relevance
“…Upon addition of ferrous sulfate (FeSO 4 ) in the medium, abundant black precipitates were immediately generated both in abiotic controls (S(0)+Na 2 S+FeSO 4 ) and in experiments conducted in the presence of cells ( Figure 1 ). In presence of T. kodakarensis , the deep dark aspect of the precipitates faded after 192 h of mineralization ( Figure 1 ), consistently with the observations reported in Gorlas et al (2022) . The abiotic controls retained their initial appearance over the entire duration of the experiments, no fading of the deep dark aspect of the precipitates occurred ( Supplementary Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Upon addition of ferrous sulfate (FeSO 4 ) in the medium, abundant black precipitates were immediately generated both in abiotic controls (S(0)+Na 2 S+FeSO 4 ) and in experiments conducted in the presence of cells ( Figure 1 ). In presence of T. kodakarensis , the deep dark aspect of the precipitates faded after 192 h of mineralization ( Figure 1 ), consistently with the observations reported in Gorlas et al (2022) . The abiotic controls retained their initial appearance over the entire duration of the experiments, no fading of the deep dark aspect of the precipitates occurred ( Supplementary Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
“…The formation of a black precipitate immediately after the addition in the medium of iron as Fe 2+ ( Figure 1 ) is caused by the precipitation of amorphous or poorly crystalline nanophases such as FeS nano-mackinawite [unambiguously detected by Rietveld refinement ( Table 2 ) and XANES ( Figure 2 and Table 1 )] and iron phosphates ( Figure 4B ; Gorlas et al, 2018 , 2022 ), the two phases forming a three-dimensional matrix observed by electron microscopy. A similar amorphous matrix is observed in the abiotic control [S(0) + Na 2 S + FeSO 4 ] at 96 h ( Supplementary Figure 3 ), identified as FeS nano-mackinawite by Rietveld refinement ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased importance of the polysulfide pathway over the sulfide pathway for pyrite formation in the presence of microorganisms was supported by the observation that S 8 0 was required for pyrite formation in incubations with the thermophilic S 8 0 -reducing species Thermococcus kodakarensis (Gorlas et al, 2022). Although that study suggested a key role for intracellular S 8 0 vesicles produced by the T. kodakarensis cells (Gorlas et al, 2022), additional abiotic controls with higher amounts of Na 2 S, more closely mimicking the conditions created by actively S 8 0 -reducing microorganisms, were not performed.…”
Section: Discussionmentioning
confidence: 95%
“…(2 mM total sulfide) (Gorlas et al, 2022), which can be expected to have precipitated immediately as FeS, making H 2 S unavailable for subsequent pyrite formation. Abiotic controls with excess of H 2 S, would have helped to assess whether the S 8 0 vesicles indeed have a so far undefined beneficial property to induce pyrite formation, or whether pyrite formation in the microbial cultures is enabled by the higher H 2 S concentrations, regardless of the form of S 8 0 in the medium (bulk or biologically produced vesicles).…”
Section: Discussionmentioning
confidence: 99%